2019
DOI: 10.1002/anie.201911842
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostibination

Abstract: Ar igid naphthalenediamine framework has been used to prepare antimony hydrides that feature LUMO shapes and energies similar to those found in secondary boranes.B y exploiting this feature,w ei ntroduce the first examples of uncatalyzed hydrostibination reactions of robust CC, C=C, C = O, and N = Nb onds as new elementary hydrometalation reactions analogous to hydroboration. These results endorse the notion of ad iagonal relationship between the lightest p-block element and the heaviest Group 15 elements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 74 publications
4
54
0
Order By: Relevance
“…22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene. The reaction proceeds under ambient conditions with near-quantitative yields (Figure 1b), 26 and is directly analogous to uncatalyzed hydroboration, furthering our unusual proposal of a "diagonal relationship" 27,28 between the lightest p-block element and heavy Group 15 metals. Despite this superficial similarity, the complexity of this simple two-component reaction was indicated by the observation that hydrostibination showed the opposite stereochemical outcomes to hydroboration.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…22,23 As part of our exploration into new structure and reactivity at antimony and bismuth centres, 24,25 we recently reported the first definitive catalyst-and additive-free addition of stibines to alkenes, alkynes, ketones, and azobenzene. The reaction proceeds under ambient conditions with near-quantitative yields (Figure 1b), 26 and is directly analogous to uncatalyzed hydroboration, furthering our unusual proposal of a "diagonal relationship" 27,28 between the lightest p-block element and heavy Group 15 metals. Despite this superficial similarity, the complexity of this simple two-component reaction was indicated by the observation that hydrostibination showed the opposite stereochemical outcomes to hydroboration.…”
Section: Introductionsupporting
confidence: 63%
“…Breunig, Tokitoh, Scheer, Power, and we have shown that primary and secondary stibines can be deprotonated in the presence of alkyllithium bases, amino bases, and alkali metals. 26,[33][34][35][36][37][38][39] In contrast, Huang has implied hydride-like reactivity for Ph2SbH in AlCl3-catalyzed hydrostibination of C=O bonds. 22 We and others have previously shown that stibines react with the trityl cation Ph3C + to yield Ph3C-H and stibenium ions, further evidencing hydridic reactivity for the Sb-H bond.…”
Section: Considered Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations